Online PD Measurement by Detecting the Pulsed Compensating Current in High Voltage Equipment - Srinangyam, Chissanupong; Pannil, Pittaya; Nimsanong, Phethai; Chuayin, Chaitawat; Thungsook, Kittisak; Pattanadech, Norasage (My University, 2022)
This paper discusses the pulsed compensating current caused by partial discharge (PD) phenomena that flows inside the electrical equipment installed in the power system. Such electrical equipment like to be the capacitive coupler in the partial discharge test circuit. In order to study the pulsed compensating current of the PD measurement, artificial PD source such as corona, surface, and internal was used in this experiment. The electrical equipment like surge arrester combined with HFCT sensor utilized to detect the PD pulse current. Furthermore, this proposed technique has been applied for online PD measurement in substations. It was found that the surge arrester could compensate for the pulse current arising from the PD source. This study will be helpful information for online PD measurement.
Keywords: HFCT; Partial discharge; PRPD; Pulsed compensating current; Surge arrester